Experimental-Theoretical Technique for Design Antifriction Polyetheretherketone Composites of Optimum Compositio; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Bochkareva S. A.; Grishaeva N. Yu.; Lyukshin B. A.; Panin S. V. Sergey Viktorovich; Matolygina N. Yu.; Panov I. L.; Nguyen Dyk An; Byakov V. (2018, 2018)
Title screen